Measurement of Social Impact of Community Empowerment Program Based Processed Product Using SBMC Maters (Study Case: Manggo Puree Fruits Up Social Business) - Dwi Purnomo; Anas Bunyamin; Asri Iswa Nurbaiti; Marlis Nawawi; Diana Sari; Wahyu Gunawan (APTA and DTIP FTP UGM, 2020)
Fruits Up designed as Agro-Industrial businesses with social business platform. Furthermore, this business is designed to provide a broad impact by connecting value chain and benefits from the village to the city. In its efforts, there are many key partners involved in the business model. Reinforcement of key partners is very important to keep the business sustainable. This research aims to find out the social impact brought by the business. The method used is descriptive with interviews in depth. To illustrate the social impacts of Fruits up Business used Social Business Model Canvas (SBMC). This research also produced a map that describe the distribution of impacts in qualitative and quantitative results from observations that done for 2 years. SBMC ripeness level measured through social impact measurement tools that designed specifically through Forum Group Discussion with stakeholders. Based on the analysis of the Social Business Model Canvas, Fruits Up successfully deliver measurable impacts to the community. Although financially fruits Up still needs to be much improved.